A Systematic Review of the Accuracy of Insulin and C-peptide Secretion Ratios During the Oral Glucose Tolerance Test to Diagnose Insulinoma - Chandra, Fransiskus Mikael; Tahapary, Dicky Levenus (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Background. Insulinoma is one of the causes of recurrent hypoglycemia, one of the chief complaints for emergency department admission. The gold standard in diagnosing insulinoma is a 72-hour fasting test which is inconvenient and inefficient as it requires hospitalization. Research has found that measurement of insulin and C-peptide during OGTT may help diagnose insulinoma. We aimed to assess the diagnostic value of OGTT in diagnosing insulinoma. Methodology. The literature search was conducted on 19 August 2022 using several databases (MEDLINE, Scopus, Embase, and ScienceDirect). All studies that measured OGTT as diagnostic tools in diagnosing insulinoma and 72-hour fasting test as reference standard were included. The quality assessment of the selected studies was based on the Centre of Evidence-Based Medicine University of Oxford and the Quality Assessment of Diagnostic Accuracy-2 tool (QUADAS-2). Analysis of the included studies was performed qualitatively. This study was registered on PROSPERO (CRD42022360205). Results. A total of two case-control studies (106 patients) were included, which were at risk of bias and low concern of applicability. Both studies demonstrated that the combination of insulin and C-peptide levels measured during OGTT had high specificity, sensitivity, positive predictive value, and negative predictive value in diagnosing insulinoma compared to the reference standard. A logistic regression model of 8.305 – (0.441 × insulin 2-h/0-h) – (1.679 × C-peptide 1-h/0-h) > 0.351 has the highest diagnostic value in one study (AUC 0.97, Sensitivity 86.5%, Specificity 95.2%, PPV 94.1, NPV 88.9). Conclusion. The measurement of 0-h and 2-h insulin and C-peptide levels during 2-h OGTT was found in two small case-control studies with a total of 106 patients to have good sensitivity and specificity. However, due to these limitations, future research is still needed to validate the potential use of OGTT for the diagnosis of insulinoma.